Frequency and treatment of ovarian cysts in adolescence - Porcu, E.; Venturoli, S.; Prato, L. Dal; Fabbri, R.; Paradisi, R.; Flamigni, C. (Archives of gynecology and obstetrics, 1994)
Ultrasound examination of the ovaries was performed monthly in the follicular phase of 139 healthy adolescents for one year. In 17 girls (12.2%) ovarian cysts spontaneously disappeared within 3 months of first observation. In 6 subjects, treatment with the combined estrogen/progestogen pill was given. The treatment was effective in 4 girls after 2-6 months while 2 subjects required surgical intervention for a cystic teratoma and a simple follicular cyst respectively. A spell of serial sonographic observation of ovarian cysts would seem appropriate in adolescents.